Herpesviruses and SARS-CoV-2: Viral Association with Oral Inflammatory Diseases - Banks, Jonathan M.; Capistrano, Kristelle J.; Brandini, Daniela A. [UNESP]; Zaidi, Filza; Thakkar, Pari; Rahat, Rani; Schwartz, Joel; Naqvi, Afsar R. (MDPI, 2024)
The oral cavity is a niche for diverse microbes, including viruses. Members of the Herpesviridae family, comprised of dsDNA viruses, as well as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), an ssRNA virus, are among the most prevalent viruses infecting the oral cavity, and they exhibit clinical manifestations unique to oral tissues. Viral infection of oral mucosal epithelia triggers an immune response that results in prolonged inflammation. The clinical and systemic disease manifestations of HHV have been researched extensively, and several recent studies have illuminated the relationship between HHV and oral inflammatory diseases. Burgeoning evidence suggests the oral manifestation of SARS-CoV-2 infection includes xerostomia, dysgeusia, periodontal disease, mucositis, and opportunistic viral and bacterial infections, collectively described as oral post-acute sequelae of COVID-19 (PASC). These diverse sequelae could be a result of intensified immune responses initially due to the copious production of proinflammatory cytokines: the so-called “cytokine storm syndrome”, facilitating widespread oral and non-oral tissue damage. This review explores the interplay between HHV, SARS-CoV-2, and oral inflammatory diseases such as periodontitis, endodontic disease, and peri-implantitis. Additionally, the review discusses proper diagnostic techniques for identifying viral infection and how viral diagnostics can lead to improved overall patient health.
Keywords: endodontic disease; gingivitis; herpesvirus; oral inflammation; peri-implantitis; periodontitis; SARS-CoV-2; viral diagnostics